The Resistance Mechanism of Mycoplasma bovis From Yaks in Tibet to Fluoroquinolones and Aminoglycosides - Niu, Jiaqiang; Yan, Mingshuai; Xu, Jinhua; Xu, Yefen; Chang, Zhenyu; Sizhu, Suolang (Frontiers in Veterinary Science, 2022)
Mycoplasma bovis (M. bovis) is one of the important pathogens for yaks. Aminoglycosides and fluoroquinolones are frequently used medications for the treatment of M. bovis. Drug-resistant strains were inevitable with the abuse of antibiotics. The resistance of M. bovis to aminoglycosides was related to the base mutations in drug target genes. Amino acid mutations at the quinolone resistance-determining region (QRDR) in gyrA, gyrB, parC, and parE conferred resistance to fluoroquinolones. In order to investigate the resistance mechanism of M. bovis from yaks in Tibet to aminoglycosides and fluoroquinolones, six frequently used antibiotics and ten clinical M. bovis strains were administered for a drug sensitivity test for in vitro-induced highly resistant strains, a drug stable-resistance test, cross-resistance test, and analysis of target gene mutations. The results showed that the clinical strains of M. bovis from yaks in Tibet had varying degrees of resistance to fluoroquinolones and aminoglycosides. The mechanism of resistance to fluoroquinolones and aminoglycosides was identified preliminarily for M. bovis from yaks: the single-site base mutation mediated the resistance of M. bovis from yaks and both base mutations led to highly resistant strains (aminoglycosides: rrs3 and rrs4; fluoroquinolones: gyrA and parC). The active efflux system results of M. bovis showed that there was no active efflux system based on fluoroquinolones and aminoglycosides expressed in M. bovis from yaks. The research could provide a reference for clinical treatment of M. bovis.